Automation of public libraries in Metro Manila an exploratory study - Rosal, Cheerly P. (Institute of Library Science, University of the Philippines Diliman, 2003)
The study was conducted to (1)explore the status of automation of the twelve public libraries in Metro Manila, (2)establish the current technology being used by these libraries, (3)know the services offered using the existing technology, and (4)provide future plans for automation each public library has.